Individuals’ Assessment of Corporate Social Performance, Person-Organization Values and Goals Fit, Job Satisfaction and Turnover Intentions - Hudson, Sarah; Bryson, Douglas; Michelotti, Marco (Relations industrielles / Industrial Relations, 2017)
Recent research in the domain of corporate social responsibility (CSR) has underlined the importance of moving away from an institutional perspective of CSR towards research at the micro-level. Such calls have insisted on the necessity of a developing a deeper, and more nuanced understanding of its impacts and mechanisms at the individual level. This paper addresses this issue by focusing on the nexus between how employees judge their companies’ actual CSR performance and how that judgement can affect individual, micro-level outcomes such as job satisfaction and turnover intentions. We study this by a consideration of how perceived fit between employees and their organization mediates the relationship between perceived corporate social performance (CSP) on the one hand, and job satisfaction and turnover intentions on the other.While there is a notion, commonly embraced in the literature, that corporate social performance can have beneficial effects on individual employee outcomes, there have not been many empirical studies looking into the mechanisms by which this occurs. Through a survey of 317 young employees from differing company sizes and sectors in Europe and Asia, we find that positive assessment of CSP does not have a direct influence on job satisfaction and turnover intention, but is mediated by person-organization fit. The latter, in turn, has a positive effect on job satisfaction and reduced turnover intention.The implications of these findings are that the achievement of efficient and effective performance in social and environmental terms reinforces the perception of employees that their values fit with those of the organization. This process then creates value in terms of increased job satisfaction and reduced employee turnover intentions. We note also that simply improving CSP objectively, without involving and raising awareness among employees, will not necessarily lead to improved perceptions of how the employee fits within the organization and the potential positive knock-on employee outcomes.